Failure to vaccinate against whooping cough. Issue 4 (April 1986) - Stevens, D; Baker, R; Hands, S
Abstract : We describe a prospective study in which we investigated why children fail to get vaccinated against whooping cough, including an assessment of the attitudes of parents and professionals and the impact of different views of the contraindications. There was considerable disagreement among the professionals on the interpretation of the contraindications to immunisation, and the commonest reason for omitting pertussis vaccine was advice from the doctor based on dubious contraindications. When faced with parents anxious about the risks of immunisation health professionals are unable to find reassurance in the list of contraindications to immunisation.